Changes in the health of adolescent athletes: A comparison of health measures collected before and during the CoVID-19 pandemic - McGuine, T. A.; Biese, K.; Hetzel, S. J.; Petrovska, L.; Kliethermes, S.; Reardon, C. L.; Bell, D. R.; Brooks, M. A.; Watson, A. M. (MedRXiv, 2021)
Context: In the spring of 2020, schools closed to in-person teaching and sports were cancelled to control the transmission of CoVID-19. The changes that took place to the physical and mental health among young athletes during this time remain unknown, however. Objective: Identify changes in the health (mental health, physical activity and quality of life) of athletes that occurred during the CoVID-19 pandemic. Design: Cross sectional study. Setting: Sample recruited via social media. Patients or Other Participants: 3243 Wisconsin adolescent athletes (age=16.2±1.2 yrs., female=58% female) completed an online survey in May 2020 (DuringCoVID-19). Health measures for this cohort were compared with previously reported data for Wisconsin adolescent athletes (n=5231, age=15.7±1.2, 47% female) collected in 2016-2018 (PreCoVID-19). Main Outcome Measure(s): Demographic information included: sex, grade and sports played. Health assessments included the Patient Health Questionnaire-9 Item (PHQ-9) to identify depression symptoms, the Pediatric Functional Activity Brief Scale (PFABS) for physical activity, and the Pediatric Quality of Life Inventory 4.0 (PedsQL) for health related quality of life (HRQoL). Univariable comparisons of these variables between groups were made via t-tests or chi-square tests. Means and 95% confidence intervals (CI) for each group were estimated by survey weighted ANOVA models. RESULTS: Compared to PreCoVID-19, a larger proportion of the During-CoVID-19 participants reported rates of moderate to severe levels of depression (9.7% vs 32.9%, p<0.001). During-CoVID-19 participants reported 50% lower (worse) PFABS scores (mean:12.2 [95%CI: 11.9, 12.5] vs 24.7 [24.5, 24.9] p<0.001) and lower (worse) PedsQL total scores compared to the PreCoVID-19 participants (78.4 [78.0, 78.8] vs. 90.9 [90.5, 91.3] p<0.001). CONCLUSIONS: During the CoVID-19 pandemic, adolescent athletes reported increased symptoms of depression, decreased physical activity and decreased quality of life compared to adolescent athletes in previous years. Key points: Adolescent athletes during CoVID-19 were three times more likely to report moderate to severe symptoms of depression compared to data collected prior to CoVID-19.